2021
DOI: 10.24875/acme.m21000194
|View full text |Cite
|
Sign up to set email alerts
|

Safety and improvement in exercise tolerance with interval training vs moderate-intensity continuous training in heart disease patient of very high cardiovascular risk

Abstract: Seguridad y mayor tolerancia al esfuerzo con entrenamiento interválico en comparación con el entrenamiento de intensidad moderada continua en cardiópatas de riesgo cardiovascular muy alto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…A clear conclusion regarding the dropout rate and level of attendance compared with other training modalities cannot be made based on the included studies, as there is not enough data, and the reported data are incomplete in some of the studies. Furthermore, the reported advantage of higher participants responsiveness to HIIT compared with MCT [30] was not demonstrated in the current review. One study demonstrated lower dropout rates in the HIIT group compared with the MCIT group (HIIT = one participant versus MCT = six participants) [42], while another study [46] reported a higher dropout rate in the HIIT group compared with the MCT group (HIIT = 11 participants versus MCT = zero participants).…”
Section: Safety Feasibility and Responsiveness Of Hiitmentioning
confidence: 60%
See 1 more Smart Citation
“…A clear conclusion regarding the dropout rate and level of attendance compared with other training modalities cannot be made based on the included studies, as there is not enough data, and the reported data are incomplete in some of the studies. Furthermore, the reported advantage of higher participants responsiveness to HIIT compared with MCT [30] was not demonstrated in the current review. One study demonstrated lower dropout rates in the HIIT group compared with the MCIT group (HIIT = one participant versus MCT = six participants) [42], while another study [46] reported a higher dropout rate in the HIIT group compared with the MCT group (HIIT = 11 participants versus MCT = zero participants).…”
Section: Safety Feasibility and Responsiveness Of Hiitmentioning
confidence: 60%
“…HIIT has been shown to improve functional capacity, muscle power, and physical performance in older individuals with and without comorbidities such as heart failure and diabetes mellitus [27][28][29]. While HIIT programs are regarded as more enjoyable and motivating than standard continuous exercise programs, they have also been shown to be safe for older adults with and without heart disease [19,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity interval training enhances the cardiac function of people with cardiovascular disease, as evidenced by increased cardiac output, beat-to-beat output, and ejection fraction [ 53 ]. However, the patient’s physical indicators and physiological responses should be closely monitored during and after HIIT [ 54 ]. Exercise intensity should be increased gradually to allow the patient to gradually adapt, ensuring patient safety and avoiding secondary morbidity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…El HIIT consiste en una serie de repeticiones de intervalos de entrenamiento de mayor intensidad intercalados con pausas de recuperación (activas o pasivas) 2,6,13 e involucra periodos de ejercicio con intensidad relativamente alta y periodos de descanso de intensidad leve 6 , con lo cual se genera menor fatiga usando de manera repetida los sistemas energéticos de menor duración, es decir, el sistema de fosfágenos y de glucólisis; además, por los periodos de descanso se logra que el volumen sistólico alcance valores elevados varias veces en la rutina 13 . El HIIT también es definido como el entrenamiento inter válico aeróbico (caminar o correr) a 85-90% del VO 2 pico o al 90-95% de la FC pico con periodos de recuperación a 60-70% de FC pico de 2 a 3 minutos 14 .…”
Section: Hiitunclassified
“…Por su parte, Pineda-García et al 13 realizaron un estudio cuasi experimental en el que incluyeron 81 pacientes con estratificación de riesgo cardiovascular alta (>2 factores de riesgo cardiovascular alto) que participaron en un entrenamiento aeróbico supervisado y fueron divididos en dos grupos: unos de HIIT de moderada intensidad (13 pacientes) con inter valos de tres minutos al 70-80% de la frecuencia cardiaca de reserva con pausas activas de tres minutos al 60-70% de la frecuencia cardiaca de reserva, otro de HIIT de alta intensidad (7 pacientes) en intervalos de tres por tres minutos con ejercicio a 80-90% de FC y las pausas activas al 70-80% de FC y otro de MICT (61 pacientes) que seguía los lineamientos de ejercicio aeróbico continuo. En dicho estudio todos los grupos realizaron ejercicio de fuerza con tres sesiones semanales (isotónicos, calentamiento e intervención multidisciplinaria) y se registró una mayor ganancia en METs (cantidad de energía que consume un individuo en situación de reposo) de carga en los pacientes del grupo HIIT de alta intensidad (86% de mejora) y en ninguno de los tipos de entrenamiento se reportaron resultados adversos, por lo que los autores llegaron a la conclusión de que el entrenamiento HIIT fue seguro y mejor tolerado en comparación con el MICT en pacientes de alto riesgo cardiovascular 13 .…”
Section: Hiitunclassified